Educating on a budget: The subsistence model of low-fee private schooling in Peru - María Balarin; Clara Fontdevila; Paola Marius; María Fernanda Rodríguez (Arizona State University, 2019)
Over the last decades, Peru has experienced an extraordinary rise of low-fee private schools (LFPSs). While global debates on the quality of this modality of schooling have been gaining currency, research on the organizational practices of LFPSs remains comparatively underdeveloped. This paper aims at identifying and describing the managerial, business and organizational practices exhibited by Peruvian LFPSs- and at understanding them in relation to the social norms and institutional arrangements specific to the context in which they operate. The study draws on a combination of archival analysis, interviews with decision-makers, and interviews with school owners and principals. The results of our research show that the specificities of the socioeconomic, cultural and regulative environments in which Peruvian LFPSs operate have led to the consolidation of a particular subsistence model of LFPS where profit-making appears to play a limited role. This model is also characterized by the low formalization of management routines, the impossibility to generate economies of scale, and the reliance on interpersonal trust as a means to reduce risk - in a context of low bureaucratization and limited regulatory oversight. We argue that, in view of the distinctly low achievement levels of Peruvian LFPSs, gaining a fine-grained understanding of their organizational practices (and the incentives they respond to) remains a relevant task, and a necessary step to devise effective policy strategies.